Dangerous cooking a study on risk aversion in household cooking fuel preference - Punzalan, Lance Lizor A. (School of Economics, University of the Philippines Diliman, 2018)
Our study aimed to investigate whether risk perception, with respect to income, education, urbanity and knowledge of usage of the fuel type, negatively affects the household cooking fuel preferences. The data set was obtained from the Household Energy Consumption Survey (HECS) 2011 and was used for the empirical analysis. The main outcome variable used in the study was a polychotomous categorical variable which tells the most preferred fuel types of the households, regardless of price and accessibility. The fuel types included in this variable are LPG, electricity, fuelwood, charcoal, and kerosene. The main explanatory variables used in the study are categorical variables for the perception on fuelwood and LPG usage being unsafe. The other explanatory variables which are all discrete are_ educational attainment, urbanity, knowledge in using LPG, and average monthly income. Different models were used in the study in order to suffice the study_s objectives. In analyzing the effects of the explanatory variables on the individual preference for each fuel type_ logit, probit, and LPM regressions were done. In finding the effects of the explanatory variables on the relative preference for each fuel type, multinomial logistic regressions were done. The empirical analysis produced results that are consistent with the Risk Aversion Theory. Perceived risk on LPG usage decreases the preference for it and increases the preference for its substitutes. In the same way, perceived risk on fuelwood usage decreases the preference for it and increases the preference for its substitutes. Other explanatory variables also presented the expected results. First, higher educational attainment translates to a higher preference for a more modern fuel type, such as LPG. Lower educational attainment on the other hand translates to a higher preference for a more primitive fuel type, such as fuelwood. Second, urban households tend to prefer more modern fuel types while rural households tend to prefer more primitive ones. Third, knowledge on LPG usage has showed positive correlation with the preference for more modern fuel types and negative correlation with the preference for more primitive ones. Lastly, higher income households tend to prefer more modern fuel types while lower income households tend to prefer more primitive ones.